2023
DOI: 10.1136/gpsych-2023-101092
|View full text |Cite
|
Sign up to set email alerts
|

Effect modifications of BMI transition and trajectory in the associations of adverse childhood experiences with new-onset dementia and its subtypes in older US adults

Ziyang Ren,
Binbin Su,
Yushan Du
et al.

Abstract: BackgroundAdverse childhood experiences (ACEs) and dementia are associated and comorbid with obesity. However, according to emerging research, the role of obesity in the association between ACEs and dementia seems controversial.AimsThis analysis aimed to explore the associations between ACEs and different dementia subtypes and the effect modification of long-term body mass index (BMI).MethodsData were obtained from the US Health and Retirement Study. Six ACEs were categorised as 0, 1 and 2 or more. All-cause d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Intervention strategies targeting the risk factors in early life could reduce the incidence of dementia or substantially delay its onset[ 52 ]. Recent studies have found that low adolescent cognitive ability[ 53 , 54 ] and adverse childhood experiences[ 55 , 56 ] have a significant association with dementia risk in later life. Depression that occurs in childhood and adolescence is often accompanied by varying degrees of cognitive impairment in attention, memory, and executive functioning, or even interrupted educational trajectories[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention strategies targeting the risk factors in early life could reduce the incidence of dementia or substantially delay its onset[ 52 ]. Recent studies have found that low adolescent cognitive ability[ 53 , 54 ] and adverse childhood experiences[ 55 , 56 ] have a significant association with dementia risk in later life. Depression that occurs in childhood and adolescence is often accompanied by varying degrees of cognitive impairment in attention, memory, and executive functioning, or even interrupted educational trajectories[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GBTM is a semiparametric model capable of classifying participants with similar patterns of depressive symptoms into clusters over time. 20 21 The best-fitting model was estimated using a three-step procedure. First, an appropriate model was selected based on the variable’s distribution.…”
Section: Methodsmentioning
confidence: 99%